Association between nitrate concentration in drinking water and rate of colorectal cancer: a case study in northwestern Iran. Issue 8 (3rd August 2022) - Nasseri Maleki, Golnoosh; Bayati Khatibi, Maryam; Khamnian, Zhila; Jalali, Zahra; Dastgiri, Saeed; Ghodrati Aroogh, Hossein
ABSTRACT: Nitrate, as a major pollutant of drinking water, is associated with colorectal cancer (CRC) and serves as an environmental health concern, especially in the districts with unregulated agriculture. In this case study in northwestern Iran, we used two databases of nitrate concentration (1999–2013) and age-standardized incidence rate (ASR) for CRC (2002–2012) from 19 counties of East Azerbaijan province. The trend and correlation between nitrate and ASR was investigated. Inverse distance weighted technique was used to spatially interpolate the maps. Expectedly, drinking water nitrate has increased throughout the province (8–20.5 mg/L) as well as the ASR for CRC of men (from 2.07 to 18.05 mg/L) and women (from 1.57 to 10.94 mg/L). While ASR for CRC of men was positively correlated to nitrate (Pearson's r = 0.624, p -value = 0.040), no statistically significant correlation was found between nitrate and ASR for women's CRC (Pearson's r = 0.289, p -value = 0.351). According to our findings, the incidence of CRC was not higher for those residing in the regions with higher nitrate, suggesting that risk factors such as genetic predisposition and diet that were not taken into account could be determinants of this pattern. However, even a small increase in CRC rate due to water nitrate could translate into a large public health concern. The incremental pattern observed in nitrate levels of different counties over the years gives the health policymakers a better perspective of the problem and how the control of water nitrate level as a CRC risk factor might contribute to the prevention of CRC.